Dose recalculation and the Dose-Guided Radiation Therapy (DGRT) process using megavoltage cone-beam CT. - Cheung J; Aubry JF; Yom SS; Gottschalk AR; Celi JC; Pouliot J; Cheung, Joey; Aubry, Jean-François; Yom, Sue S; Gottschalk, Alexander R; Celi, Juan Carlos; Pouliot, Jean (International Journal of Radiation Oncology, Biology, Physics, 2009)
Purpose: At the University of California San Francisco, daily or weekly three-dimensional images of patients in treatment position are acquired for image-guided radiation therapy. These images can be used for calculating the actual dose delivered to the patient during treatment. In this article, we present the process of performing dose recalculation on megavoltage cone-beam computed tomography images and discuss possible strategies for dose-guided radiation therapy (DGRT). Materials and Methods: A dedicated workstation has been developed to incorporate the necessary elements of DGRT. Patient image correction (cupping, missing data artifacts), calibration, completion, recontouring, and dose recalculation are all implemented in the workstation. Tools for dose comparison are also included. Examples of image correction and dose analysis using 6 head-and-neck and 2 prostate patient datasets are presented to show possible tracking of interfraction dosimetric endpoint variation over the course of treatment. Results: Analysis of the head-and-neck datasets shows that interfraction treatment doses vary compared with the planning dose for the organs at risk, with the mean parotid dose and spinal cord D(1) increasing by as much as 52% and 10%, respectively. Variation of the coverage to the target volumes was small, with an average D(5) dose difference of 1%. The prostate patient datasets revealed accurate dose coverage to the targeted prostate and varying interfraction dose distributions to the organs at risk. Conclusions: An effective workflow for the clinical implementation of DGRT has been established. With these techniques in place, future clinical developments in adaptive radiation therapy through daily or weekly dosimetric measurements of treatment day images are possible.